2022
DOI: 10.1136/jclinpath-2021-208053
|View full text |Cite
|
Sign up to set email alerts
|

Preference of grade and lymphovascular invasion over invasive size measurement in stage I lung adenocarcinoma

Abstract: AimsAlthough it is necessary to measure the invasive size of lung adenocarcinoma with a lepidic component, it is not uncommon to have trouble in measuring the invasive size of lung adenocarcinoma. This study examined whether there were other stronger prognostic factors than invasive size.MethodsWe characterised the clinicopathological features associated with recurrence-free survival (RFS) of 686 patients with the pathological stage (p-Stage) I lung adenocarcinoma. Moreover, we compared the area under the curv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Tsutani et al reported similar results that invasive size was the risk factor and associated with more malignant behavior ( 14 ). Conversely, Itami et al demonstrated that lung cancer grade, lymphatic and vascular invasion are more significant prognostic factors than tumor invasive size in stage I lung adenocarcinoma ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tsutani et al reported similar results that invasive size was the risk factor and associated with more malignant behavior ( 14 ). Conversely, Itami et al demonstrated that lung cancer grade, lymphatic and vascular invasion are more significant prognostic factors than tumor invasive size in stage I lung adenocarcinoma ( 15 ).…”
Section: Discussionmentioning
confidence: 99%